2009
DOI: 10.1002/mabi.200900135
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Polymer Nanoparticles: Characterization and Assessment as New Drug Carriers

Abstract: An amino-acid-based hydrophobically modified biocompatible copolymer, poly[(sodium N-acryloyl-L-valinate)-co-(N-octylacrylamide)] was synthesized and characterized. Techniques such as fluorescence probes, DLS, and TEM were used to investigate its aggregation behavior in aqueous solution. The copolymer was observed to form micellar aggregates having diameters in the nanometer range in aqueous solution (pH = 8) through inter-chain hydrophobic association. This behavior was found to be similar to that of poly[(so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…A good correlation coefficient (R 2 = 0.99) was observed for both KTP and NPX. The resulting release exponent value (n) < 0.5 confirmed diffusion based drug release mechanism for this polymeric system (Dutta et al, 2009b). For both the drugs, it was observed that the kinetic constant k decreased upon increase of pH from 5.0 to 7.4 suggesting faster release (about 1.5 times) at pH 7.4.…”
Section: In Vitro Drug Releasesupporting
confidence: 59%
See 3 more Smart Citations
“…A good correlation coefficient (R 2 = 0.99) was observed for both KTP and NPX. The resulting release exponent value (n) < 0.5 confirmed diffusion based drug release mechanism for this polymeric system (Dutta et al, 2009b). For both the drugs, it was observed that the kinetic constant k decreased upon increase of pH from 5.0 to 7.4 suggesting faster release (about 1.5 times) at pH 7.4.…”
Section: In Vitro Drug Releasesupporting
confidence: 59%
“…Solubilization studies were carried out following our previous report (Dutta et al, 2009b). Briefly, the NSAIDs were dissolved in chloroform in screw-caped test tube.…”
Section: Solubilization Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the hydrophobic drugs when administered to the body are often precipitated and degraded in the blood stream without reaching the target zone, and thus cause severe side affects (Dutta et al, 2009). TQ, the major biologically active component isolated from a traditional medicinal herb, Nigella sativa Linn., is a potential chemopreventive and chemotherapeutic compound (El-Mahdy et al, 2005).…”
Section: In Vitro Drug Releasementioning
confidence: 99%